1986
DOI: 10.1136/adc.61.5.464
|View full text |Cite
|
Sign up to set email alerts
|

Growth in thyrotoxicosis.

Abstract: SUMMARY To study the effect of thyrotoxicosis on growth, 46 children and adolescents presenting with thyrotoxicosis have been reviewed and followed up for several years, in most cases until adult height was achieved. At presentation the children were underweight for height but were above expected heights even if already well advanced in puberty. Despite bone ages often being very advanced at diagnosis, the condition had no adverse effect on ultimate stature, which was commonly greater than that expected on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 9 publications
4
28
0
1
Order By: Relevance
“…Childhood thyrotoxicosis has been documented to be more common in our locality and the current study included a large group of patients such that detailed analyses of their growth were possible. Studies have showed that children with thyrotoxicosis were tall for age at presentation and their bone ages tended to be advanced [2,8]. Buckler et al reported that a group of 40 girls with thyrotoxicosis at presentation had a mean height SDS of +0.75 [2].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Childhood thyrotoxicosis has been documented to be more common in our locality and the current study included a large group of patients such that detailed analyses of their growth were possible. Studies have showed that children with thyrotoxicosis were tall for age at presentation and their bone ages tended to be advanced [2,8]. Buckler et al reported that a group of 40 girls with thyrotoxicosis at presentation had a mean height SDS of +0.75 [2].…”
Section: Discussionmentioning
confidence: 96%
“…Accelerated bone maturation and growth velocity in children with thyrotoxicosis have also been reported [8]. There are, however, only a few reports of the eect of thyrotoxicosis on ®nal height [1,2,9]. Only one report attempted to compare the ®nal heights of aected children with their target heights [2].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Hypothyroidism slows longitudinal bone growth and endochondral ossification, while hyperthyroidism accelerates both processes [39, 40]. In hypothyroid animals, there is a decrease in the heights of the proliferative and hypertrophic zones, and a decrease in chondrocyte proliferation, chondrocyte hypertrophy, and vascular/bone cell invasion [41].…”
Section: Thyroid Hormonementioning
confidence: 99%
“…2). Such linear growth acceleration is not as pronounced in older children with hyperthyroidism due to either Graves' disease [28,29] or to an autonomous adenoma (our patient 2). A distinctive feature of autonomous adenomas is the absence of ophthalmopathy and the absence of antibodies to the TSHR, which are the hallmark of Graves' disease.…”
Section: Clinical Presentation Of 16 Patientsmentioning
confidence: 95%